2010
DOI: 10.1136/bjsm.2010.078725.68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 weeks resistance training on plasma visfatin in middle aged men

Abstract: Visfatin, a novel adipokine, is increased in obesity. It is not well known whether resistance training induced change in adipose tissue and blood lipids decrease plasma visfatin; thus, the purpose of this study was to examine the effect of 8 weeks' resistance training on plasma visfatin in middle-aged men. Nineteen healthy middle-aged men (aged 39.2 ± 4.6 years; height 173.8 ± 6.5 cm; BMI 24.8 ± 2.8 kg/m 2 ; mean ± SD) participated as subjects in this study. The subjects were randomly assigned to training grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These data revealed that chronic exercise training decreased visfatin levels in individuals with obesity. [350][351][352][353][354][355] Negative energy balance is one of the mechanisms whereby visfatin level can rapidly increase after exercise. 356 Moreover, blood visfatin concentrations correlated with exercise duration 357 and the exercise-induced energy defect induces visfatin mRNA expression in adipose tissues.…”
Section: Effects Of Acute and Chronic Exercise On Visfatinmentioning
confidence: 99%
“…These data revealed that chronic exercise training decreased visfatin levels in individuals with obesity. [350][351][352][353][354][355] Negative energy balance is one of the mechanisms whereby visfatin level can rapidly increase after exercise. 356 Moreover, blood visfatin concentrations correlated with exercise duration 357 and the exercise-induced energy defect induces visfatin mRNA expression in adipose tissues.…”
Section: Effects Of Acute and Chronic Exercise On Visfatinmentioning
confidence: 99%
“…One of the reasons for this decrease is the increase in insulin sensitivity, which reduces serum levels. Many studies have shown that physical activity reduces the serum level of visfatin [34][35][36]. For example, Haider et al examined the effect of aerobic exercise on visfatin levels in 18 patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Since visfatin is secreted from visceral adipose tissue, exercise, due to its effects on the reduction of visceral adipose tissue of the body and as a result of improvement of some adipokines, can also be effective in reducing (25). In contrast, McKenzie et al (2008) observed increased plasma visfatin after 6 months of aerobic training at 70% of maximum heart rate in healthy individuals and patients with impaired glucose (26).…”
Section: Introductionmentioning
confidence: 99%